The effect of reclining position on swallowing function in stroke patients with dysphagia - Benjapornlert, Paitoon; Kagaya, Hitoshi; Inamoto, Yoko; Mizokoshi, Eriko; Shibata, Seiko; Saitoh, Eiichi (Journal of oral rehabilitation, 2020)
Background Dysphagia is a common problem in patients with a history of stroke. In Japan, a reclined position is commonly used as a compensatory technique to address this problem. Objective To evaluate the effect of reclined position on swallowing function in patients with stroke who had dysphagia. Methods A retrospective analysis was carried out on the videofluoroscopic examination of swallowing (VF) of 4ml honey‐thick liquid swallows collected over 9 years. Penetration‐aspiration scale (PAS) and residue scores were compared for the following: a body position at 90° upright (90°U) and 60° reclining (60°R) groups, as well as 60°R and 45° reclining (45°R) groups. Results Two hundred and five records from 98 subjects were reviewed. These included patients with ischaemic stroke (62%), haemorrhagic stroke (32%) and subarachnoid haemorrhage (6%). PAS scores were lower when the body was in a more reclined position (P < .001). The amount of residue in the valleculae and pyriform sinus also reduced in the more reclined position (P < .001). The deeper bolus head at swallowing onset was positively correlated with severe PAS (P < .001). Conclusions These findings suggest that in patients with stroke who had dysphagia, a reclined position may be useful in reducing the risk of penetration and aspiration, and in decreasing the amount of residue in the pharyngeal area. The depth of the bolus head at the onset of swallowing increases the severity of penetration and aspiration.